2007
DOI: 10.1111/j.1743-6109.2007.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Deficiency and Abnormal Penile Duplex Parameters in Obese Men with Erectile Dysfunction

Abstract: Introduction The clinical identification of metabolic syndrome is based on measures of abdominal obesity, atherogenic dyslipidemia, elevated blood pressure, and glucose intolerance. However, the impact of hypogonadism associated with obesity on penile hemodynamics is not well investigated. Aim In this retrospective study, we sought to evaluate the effect of obesity on serum total testosterone (TT) level and penile duplex para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 65 publications
(64 reference statements)
2
32
1
2
Order By: Relevance
“…Several reports showed that the accumulation of fatty tissue in men was associated with decreased total, free T, and increased E 2 serum levels (17,18). Zohdy et al (19) reported significant negative correlation between BMI and serum total T. Zorn et al (20) demonstrated a link between leptin and testicular function, independent of FSH and LH, possibly involving T and SHBG through a regulation of Leydig cell function. Goncharov et al (21) concluded that there was a negative relationship between serum T and leptin in obese men.…”
Section: Discussionmentioning
confidence: 96%
“…Several reports showed that the accumulation of fatty tissue in men was associated with decreased total, free T, and increased E 2 serum levels (17,18). Zohdy et al (19) reported significant negative correlation between BMI and serum total T. Zorn et al (20) demonstrated a link between leptin and testicular function, independent of FSH and LH, possibly involving T and SHBG through a regulation of Leydig cell function. Goncharov et al (21) concluded that there was a negative relationship between serum T and leptin in obese men.…”
Section: Discussionmentioning
confidence: 96%
“…In a recent study by Zhody et al (2007), the relationship between erectile dysfunction, androgen deficiency, and MS was solidified by another means: the measurement of BMI. With increasing BMI, the incidence of erectile dysfunction and hypogonadism increased in a strong positive correlation.…”
Section: Hypogonadism and Msmentioning
confidence: 99%
“…83 Obesity has also been related to lower testosterone and poor penile hemodynamics. 84 As anticipated, the metabolic syndrome and insulin resistance are associated with ED. 85,86 In the Massachusetts Male Aging Study, ED was predictive of the presence of the metabolic syndrome only in nonobese men.…”
Section: Obesity Metabolic Syndrome Type 2 Diabetes Mellitus and Lomentioning
confidence: 99%